2019
DOI: 10.4082/kjfm.17.0084
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Breastfeeding Duration and Reproductive Factors with Sarcopenia in Elderly Korean Women: A Cross-Sectional Study from the Korea National Health and Nutrition Examination Survey 2010–2011

Abstract: Background Several studies have suggested that breastfeeding has a positive effect on long-term obesity, diabetes, hypertension, and hyperlipidemia. This study aimed to examine maternal bone health, muscle mass, and obesity based on breastfeeding duration. Methods This study was based on the Korea National Health and Nutrition Examination Survey 2010–2011. We selected 2,027 elderly women by screening survey participants with a history of delivery. Multivariate logistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Similar to that reported by several previous sarcopenia studies using KNHNES data that were published in the Korean Journal of Family Medicine, [6][7][8][9][10][11] sarcopenia was found to result from multiple factors, and breastfeeding is also likely to affect sarcopenia along with other childbirth parameters.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…Similar to that reported by several previous sarcopenia studies using KNHNES data that were published in the Korean Journal of Family Medicine, [6][7][8][9][10][11] sarcopenia was found to result from multiple factors, and breastfeeding is also likely to affect sarcopenia along with other childbirth parameters.…”
supporting
confidence: 87%
“…In this issue, Kim et al 6) analyzed the association between the breastfeeding period and sarcopenia using data from the Korea National Health and Nutrition Examination Survey (KNHNES) 2010-2011. They showed that sarcopenia has a negative association and obesity has a positive association with prolonged breastfeeding in women older than 60 years and that there was a positive association between the duration since last delivery and sarcopenia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Breast milk contains all the necessary nutrients for an infant’s first 6 months of life, provides immunity to disease through maternal antibodies, increases intelligence and likely reduces overweight and diabetes (Horta, 2019 ; Victora et al, 2016 ). For women, breastfeeding protects against breast cancer, improves bone health, helps to manage birth spacing, and may protect against ovarian cancer and type 2 diabetes (Binns et al, 2016 ; Chowdhury et al, 2015 ; Grizzo et al, 2020 ; Kim et al, 2019 ; Rollins et al, 2016 ; Victora et al, 2016 ; Walters et al, 2019 ; Wiklund et al, 2012 ). Globally, if all infants were breastfed it could save nearly 850,000 lives by averting an estimated 823,000 child deaths and 20,000 maternal deaths due to breast cancer (Victora et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Less is known about potentially modifiable determinants of handgrip strength such as breastfeeding, despite the growing recognition of its clinical importance. One study analyzed data from the Korea National Health and Nutrition Examination Survey 2010–2011 and found that the odds ratios of developing sarcopenia decreased with increasing breastfeeding duration [ 10 ]. To our knowledge, that was the only study that has examined this relationship and there is a need to explore this topic further.…”
Section: Introductionmentioning
confidence: 99%